Influence of primary tillage on agrochemical indicators of soil fertility - Dubovik Dmitry (EDP Sciences, 2021)
The influence of primary tillage practices (plowing, subsurface tillage, surface tillage, direct sowing (No-till)) on the indicators of soil fertility of typical chernozem in Kursk Region on peas was studied. It was found that with the minimization of tillage humus content in the soil increased, especially in the upper 0-10 cm layer. Acidification of arable soil layer was noted when plowing was used. The content of mobile phosphorus, as well as the degree of its mobility, significantly increased with boardless tillage methods in comparison with moldboard plowing. The maximum amount of exchangeable potassium and the degree of its mobility were in case of direct sowing. The highest level of mineral nitrogen in the layer of 0-20 cm was formed in case of plowing, and its minimum level was formed in case of direct sowing. When tillage was minimized, the topsoil was differentiated by the content of mobile forms of copper, zinc and manganese. In a layer of 0-10 cm, combined tillage, surface tillage and direct sowing increased the content of mobile trace elements compared to a layer of 10-20 cm. When plowing was used as a primary tillage method, the content of mobile copper, zinc and manganese was higher in the layer of 10-20 cm.